Relating a gluon mass scale to an infrared fixed point in pure gauge QCD - Aguilar, A. C. [UNESP]; Natale, A. A. [UNESP]; Rodrigues da Silva, P. S. [UNESP] (American Physical Society (APS), 2003)
The condition for the global minimum of the vacuum energy for a non-Abelian gauge theory with a dynamically generated gauge boson mass scale which implies the existence of a nontrivial IR fixed point of the theory was shown. Thus, this vacuum energy depends on the dynamical masses through the nonperturbative propagators of the theory. The results show that the freezing of the QCD coupling constant observed in the calculations can be a natural consequence of the onset of a gluon mass scale, giving strong support to their claim.
Keywords: Approximation theory; Calculations; Condensation; Equations of motion; Fermions; Functions; Infrared radiation; Molecular dynamics; Infrared fixed point; Renormalization group equation; Schwinger Dyson equations; Vacuum energy; Quantum theory